Connection to Country – Place-based Learning Initiatives Embedded in the Charles Sturt University Bachelor of Law - Annette R. Gainsford (Legal Education Review, 2019)
Place-based learning is receiving widespread global approval for the way in which it effectively engages with local Indigenous communities. Charles Sturt University has made significant community partnerships to inform their law education curriculum. These partnerships include an “Elders in Residence” program to incorporate Indigenous place-based learning pedagogy into the teaching of core law curriculum. Such programs recognise that Indigenous Elders hold a unique place in community as the keepers of cultural knowledge. Law students engage with Indigenous knowledges to consider multiple perspectives of the law, this learning enabling students to critically reflect on their own positioning and cultural bias. The epistemological value of Indigenous knowledges is explored through the lens of justice and self-determination to equip law graduates with knowledge, skills and the competence to apply this learning to their own personal and professional practice.